2009
DOI: 10.1242/jcs.054494
|View full text |Cite
|
Sign up to set email alerts
|

Eeyarestatin I inhibits Sec61-mediated protein translocation at the endoplasmic reticulum

Abstract: Results ESSupplementary material available online at

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
145
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(154 citation statements)
references
References 40 publications
8
145
1
Order By: Relevance
“…Each of these steps could presumably prevent the completion of HC translation, thus resulting in rapidly degraded translation intermediates. Recently, the small molecule inhibitor eeyarestatin 1 (ES 1 ) was shown to efficiently inhibit protein translocation and prevent transfer of the RNC from the SR to SEC61 (10). In contrast, ES 1 did not prevent docking of the SRP/RNC to the SR.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Each of these steps could presumably prevent the completion of HC translation, thus resulting in rapidly degraded translation intermediates. Recently, the small molecule inhibitor eeyarestatin 1 (ES 1 ) was shown to efficiently inhibit protein translocation and prevent transfer of the RNC from the SR to SEC61 (10). In contrast, ES 1 did not prevent docking of the SRP/RNC to the SR.…”
Section: Resultsmentioning
confidence: 99%
“…Eeyarestatin 1 (ES 1 ) and eeyarestatin R35 (ES R35 ) were kind gifts from Stephen High (University of Manchester, Manchester, United Kingdom). Eeyarestatin treatments were based on methods previously described (10). TRFs in culture were treated with dimethyl sulfoxide (DMSO) or 10 M of the proteasome inhibitor MG132 for 4 h, followed by treatment with DMSO, 10 M ES 1 , or 10 M ES R35 for 1 h in the continuing presence of DMSO or MG132.…”
Section: Methodsmentioning
confidence: 99%
“…A general translocation inhibitor is eeyarestatin, a chemical most likely binding to the translocon and preventing the transfer of the nascent-chain-ribosome complex from the SRP-SRP receptor targeting complex to the translocon in mammalian cells (Cross et al, 2009). Apratoxin A, a cyanobacterial metabolite, has been shown to inhibit cotranslational translocation in vitro (Liu et al, 2009), but the blocked step is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Because the participation of ERAD could not be assessed definitively from our siRNA data, we addressed the issue using the chemical inhibitor, Eeyarestatin 1 (Eer1), which interacts with p97 to regulate ERAD negatively, resulting in the accumulation of polyubiquitinated intermediates (43,44). It has also been suggested that Eer1 inhibits Sec61-mediated protein translocation, because it targets a component of the Sec61 complex that forms the membrane pore of the ER translocon (45). KB cells incubated with Eer1 and A B Fig.…”
Section: Resultsmentioning
confidence: 99%